Governance and Control of Data and Digital Economy in the European Single Market Legal Framework for New Digital Assets, Identities and Data Spaces - Pastor Sempere, Carmen; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
In an era where the digital realm is evolving at an unprecedented pace, the legal framework must adapt accordingly to ensure effective governance and control. This open access book explores the intricate web of regulations governing new digital assets, identities, and data spaces within the European Single Market. Through a comprehensive exploration of emerging concepts, it provides clarity amidst complexity and empowers stakeholders to navigate the evolving digital landscape with confidence, making it essential reading for legal professionals, policymakers, regulators, academics, and industry practitioners. The book explains the need for legal adaptations to incorporate new technologies in the European Union, focusing on regulating Distributed-Ledger Technologies (DLT/Blockchain) and crypto-assets through the MiCA Regulation. It discusses the challenges and opportunities involved in ensuring stability and user protection and investigates the regulatory frameworks for Asset-Referenced Tokens, E-money Tokens, Utility Tokens, and Non-Fungible Tokens (NFTs). It also addresses related topics such as artificial intelligence, digital identities, data spaces, and cyber-security, providing an analysis rooted in European law that points to the European Roadmap to the Digital Decade for 2030. It deals with the European Digital Identity in the eIDAS2 Regulation and the Artificial Intelligence Act, both adopted in 2024, providing a lege ferenda perspective. Additionally, the book examines Open Data and Open Finance, emphasizing their roles in promoting competition and innovation while addressing data privacy and security concerns. It covers the implications and challenges of Digital Money and Digital Payments, particularly in the context of the Digital Euro project, the impact on monetary policy and financial inclusion, and the European Digital Identity $1 (Bthe EU Digital Identity Wallet, EUDI $1 (Benabling mutual recognition of electronic identification systems across EU countries.s
Part I. Recent Technological and Legal Developments -- Introduction. The legal framework for new digital assets, identities, and data spaces. -- A Regulatory Framework for Legal Ecosystems in the Context of Emerging Web-based Systems and the European AI Value Chain Regulations -- Proprietary Digital Assets Property under European Soft Law -- Crypto Assets and Financial Data Space Regulation in the EU$1 (Bs hybrid system of hard and soft law -- Web Technologies for Decentralized Identity -- The National Security Framework as a Cybersecurity Reference for Information Cryptosystems -- Part II. New Assets: Assets Regulated in MiCA -- Regulating Stablecoins in the European Union. Asset-Referenced Tokens and E-money Tokens in MiCA -- Electronic Money Tokens under the MiCA Regulation -- Utility Tokens and their regulation under MiCA -- Crypto-asset Service Providers. Harmonised Framework vs. Risk of Unlevel Playing Field -- Crypto-asset White Papers and Marketing Communications Post the MiCA Regulation -- Regulating Market Abuse in Crypto Assets -- Part III. New Assets: Subjects and Assets not Regulated in MiCA -- Current and Future Central Bank Digital Currency (CBDC) Projects -- The Digital Euro Package: from Legal Tender to Payment Service Providers -- PSD3 and the Regulation on Payments Services in the Context of Crypto-Assets as a Means of Payment -- The Non-Financial Crypto-Asset Market: Copyright in Art Non-Fungible Tokens -- Domestic Tax Law in the Face of the Crypto Economy: Challenges Going Forward -- Part IV. New Digital Spaces and Identities -- eIDAS, eIDAS 2, ARF and the European Union Digital Identity Wallet -- Digital Identity in a European User-Centric Ecosystem and its similarities with the Digital Euro proposal -- 'Human Digital Twins' on the Blockchain: Challenges and Opportunities for Digital Identity and Privacy -- The Implementation of U-space: Open Challenges from the Legal-Private Perspective.s
Keywords: Information technology -- Law and legislation; Mass media -- Law and legislation; Commercial law; European Economic Community; Law and economics; IT Law, Media Law, Intellectual Property; European Economic Law; Law and Economics